Urethroscopy evacuation of glue stick polyembolokoilomania: a case report - Sabudi, I Made Nugraha Gunamanta; Irzan, Muhammad Anwar; Ghinorawa, Tanaya (Published by Universitas Gadjah Mada, 2025)
Insertion of a foreign body is an uncommon case in the urology emergency. It was reported one of the abnormal habits called polyemobolokoilomania, which involves inserting strange things into the self-body orifice, especially the urethra in the urological case. A male 56 yo came with a history of inserting a glue stick on his external urethral orifice and complained of dysuria. By physical examination, palpated solid things 6 cm from the external urethral orifice. The patient then planned to undergo urethroscopy and found the glue stick along 27 cm. Urethroscopy successfully evacuated the whole glue stick, and a silicone catheter 18 Fr was applied to monitor the urine. The next 2 wk, the indwelling catheter was removed, and the patient could normally urinate. Glue stick insertion is one of the things that is commonly inserted by polyembolokoilomania, or the act of insertion a foreign body into a human orifice. Psychological and psychiatric aspects also need to be evaluated, because the patient could have mental health issues that need to be treated to prevent recurrent habits in the future. Physical examination of foreign bodies could be found when palpated along the penis. Further diagnostic tools like BNO could be conducted if there was no clear information from history taking (patient dishonest or unable to communicate) and in doubt by physical examination. The approach to evacuation could be varied, it could be evacuated by a milking procedure, endourology using a urethroscope, or open surgery. Insertion of strange things or polyembolokoilomania was an uncommon case in a urology emergency setting. The treatment focuses on evacuating the foreign body, and the patient can urinate normally. Psychological and psychiatric aspects also need to be followed up to prevent recurrent habits as a risk factor for repeated cases.